POLÍTICA DE ASSISTÊNCIA ESTUDANTIL NA UNIVERSIDADE FEDERAL DO PAMPA CAMPUS JAGUARÃO/RS (Razão e Fé, 2022)
This paper intends to discuss the policy of student assistance (PAE) at the Federal University of Pampa – UNIPAMPA/Jaguarão Campus, and it has the main purpose of identifying by which means the institution throughout its student assistance programs survey the areas of aiding established by article 3, paragraph 1, of the National Student Assistance Program (PNAES) in times of displacement of Brazilian public education. In accord with changes that occurred in Brazilian higher public education as a result of the expansion and interiorisation of universities and federal institutes and the establishment of affirmative action public policies. These policies permitted more democratic access to higher education and changed significantly part of the profile of humbler undergraduate students, which came from public schools and newcomers from racial and social cotes and demands effective student assistance policies.